24. An analysis of the National Institutes of Health All of Us Research Database: Sociodemographic Disparities Among Patients Who Received Vaccinations. (4th December 2021) - Ng, Ding Quan; Jia, Stanley; Cadiz, Christine; Wisseh, Cheryl; Nguyen, Megan H; Lee, Joyce; McBane, Sarah; Nguyen, Lee; Chan, Alexandre; Hurley-Kim, Keri
Abstract: Background: The National Institutes of Health All of Us (AoU) research program is building a diversified database of 1 million+ adult subjects. With this database, we seek to describe the sociodemographic characteristics of those with documented vaccinations. Methods: The AoU recruited subjects ≥ 18 years beginning in 2018. Eligible subjects were subsequently divided into five vaccine cohorts based on their vaccine history [influenza, hepatitis B (HepB), pneumococcal (Pneu) < 65, Pneu ≥ 65, human papillomavirus (HPV)]. The vaccine cohorts were compared to the general AoU cohort. Subjects in the influenza cohort had documented influenza vaccinations from 09/2017-05/2018. Other vaccine cohorts comprised subjects with ≥ 1 lifetime record(s) of vaccination by 12/2018. The Pneu < 65 and ≥ 65 cohorts comprised those who received pneumococcal vaccination before or after (inclusive) 65 years old, respectively. Descriptive statistics for all cohorts were generated using survey and electronic health record (EHR) data. Results: We analyzed 315297 subjects in the AoU dataset R2020Q4R2. The cohort sizes were: influenza (n=15346), HepB (n=6323), HPV (n=2125), and Pneu (< 65 n=15217; ≥65 n=15100). For all vaccine cohorts, comparing the 95% confidence intervals (CIs), the proportions of whites and non-Hispanics/Latinos were statistically higher than the general AoU cohort, the largest being from the Pneu ≥ 65 cohort (Table 1). For educational attainment, the Pneu < 65 (36.5%) had the smallest proportion of college or advanced degree graduates while the largest was observed in the Pneu ≥ 65 cohort (59.0%). The proportions of subjects with < &10k in annual household income (AHI) were largest among Pneu < 65 (17.1%) and smallest among Pneu ≥ 65 (3.8%). In contrast, the largest proportion of subjects with ≥ &100k AHI was among Pneu ≥ 65 (25.3%) and the smallest among Pneu < 65 (15.8%). Table 1. Sociodemographic characteristics of subjects in the All of Us research program based on vaccine receipt Conclusion: Racial and ethnic disparities in vaccinations were apparent. Pneumococcal vaccination at age 65 years and above was more prevalent among white, non-Hispanic/Latino subjects who were also more educated and affluent. Conversely, those receiving pneumococcal vaccination before age 65 years were less educated and had lower AHI. Disclosures: All Authors : No reported disclosures